Introduction of Halqi Letters in Tajweed Science Through Song Media at TPQ Nilasari Gonilan Sukoharjo - Hafid, Ruhyan Abdul; Nurrohim, Ahmad; Kurniawan, Ade; Abdullah, Muhammad Yusuf; Ghifari, Muhammad Faiq Al; Putra, Dede Satria; Hakim, Qois Abdul (Universitas Muhammadiyah Surakarta, 2023)
This research was motivated by the results of observations and research experiences that the learning process at Qur'an Education Park Nilasari Gonilan teaching materials used by teachers in the introduction of tajweed still use modules without using additional teaching materials. In addition, in the learning process, teachers still use the sorogan method and do not use learning media. As a result, students are less involved in the learning process so they do not understand the material of tajweed. Based on these facts, researchers conducted a study that aimed to improve children's ability to recognize halqi letters in tajweed using songs. This research method uses a descriptive method. The data collection instrument in this study used observation guidelines and documentation. The subjects in this study were 22 children, consisting of 10 girls and 12 boys. The location used in the study was the Nilasari Gonilan Qur'an Education Park. Research on the recognition of halqi letters with the medium of this song obtained very good results, Evidenced by the development of children in understanding halqi letters.